2018
DOI: 10.1016/j.ecns.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Debriefing Methods after a Virtual Simulation: An Experiment

Abstract: Background: Numerous studies support debriefing after an in-person simulation experience. However, there is little understanding about effective debriefing methods after a virtual simulation. Method: An experimental study was conducted to examine various debriefing methods. Participants completed a virtual gaming simulation and were randomly assigned to one of three debriefing methods: in person, virtual, and self. Results: Within groups, students made significant knowledge and self-efficacy gains, and all gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 26 publications
1
43
0
5
Order By: Relevance
“…Survey results related to our research indicated that IP, VD, and SD led to positive debriefing experiences and comparable gains in knowledge and self-efficacy (Verkuyl et al, 2018). Our focus-group results expand on this and highlight the need for research to elucidate how defusing, discovering, and deepening unfold in various debrief formats.…”
Section: Discussionsupporting
confidence: 64%
“…Survey results related to our research indicated that IP, VD, and SD led to positive debriefing experiences and comparable gains in knowledge and self-efficacy (Verkuyl et al, 2018). Our focus-group results expand on this and highlight the need for research to elucidate how defusing, discovering, and deepening unfold in various debrief formats.…”
Section: Discussionsupporting
confidence: 64%
“…Our finding regarding the importance of debriefing in the VGS process supports Crookall’s (2014) argument that debriefing is a crucial component, it optimizes learning after a VGS and effective debriefing requires training. Recent studies support other debriefing options besides the usual in-person small group debrief; they include self-debrief, virtual synchronous debrief and asynchronous debrief (Gordon, 2017; Miller et al, 2018; Verkuyl et al, 2018). Educators have options when it comes to ways to debrief a VGS.…”
Section: Discussionmentioning
confidence: 99%
“…Available research suggests that using VSGs as a presimulation activity paired with an instructor-led debriefing strategy can help students ready their knowledge and understanding before a live simulation experience (Keys, Luctkar-Flude, Tyerman, Sears, & Woo, 2020;Luctkar-Flude et al, 2018). There is also evidence to support alternative debriefing methods after a VSG, such as self-debriefing and virtual synchronous debriefing (Verkuyl et al, 2018). What has not been studied is the effectiveness of asynchronous virtual debriefing after engagement in a VSG, specifically in relation to how it impacts student anxiety and self-confidence in relation to developing CDM.…”
Section: Review Of the Literaturementioning
confidence: 99%